PERANAN KOMUNIKASI DALAM KEPEMIMPINAN PEMERINTAHAN DAN PARTISIPASI MASYARAKAT - Linda Christine S. Paembonan (Sociae Polites, 2011)
AbstractThe role of communication in the government’s leadership in an attempt to influence,move, guide and direct its community or follower is a very important factor for therealization of the goals set. Government leaders as a mover and a good communicator willclarify perceptions and convince his followers to engage and active participate in thedevelopment activities; all at once as a proof that government is practicing the communitybaseddevelopment or it is so called development from, by and for the people.Keywords: Communication role, Government leadership, Community-based development.